New roots in America's sacred ground : religion, race, and ethnicity in Indian America - Joshi, Khyati Y., 1970- (Rutgers University Press, 2006)
In this compelling look at second-generation Indian Americans, Khyati Y. Joshi draws on case studies and interviews with forty-one second-generation Indian Americans, analyzing their experiences involving religion, race, and ethnicity from elementary school to adulthood. As she maps the crossroads they encounter as they navigate between their homes and the wider American milieu, Joshi shows how their identities have developed differently from their parents' and their non-Indian peers' and how religion often exerted a dramatic effect. The experiences of Joshi's research participants reveal how.
Keywords: East Indian Americans -- Ethnic identity.; East Indian Americans -- Religion.; East Indian Americans -- Social conditions.; Religious minorities -- United States -- Social conditions.; Ethnicity -- United States.; United States -- Religion.; United States -- Race relations.; United States -- Ethnic relations.; Religion and sociology -- United States.; East Indian Americans.; Ethnicity.; Religion and sociology.; Religious minorities.; Américains d'origine indienne -- Identité ethnique.; Américains d'origine indienne -- Religion.; Américains d'origine indienne -- Conditions sociales.; Minorités religieuses -- États-Unis -- Conditions sociales.; Ethnicité -- États-Unis.; États-Unis -- Religion.; États-Unis -- Relations raciales.; États-Unis -- Relations interethniques.; Sociologie religieuse -- États-Unis.; Américains d'origine indienne.; Ethnicité.; Sociologie religieuse.; Minorités religieuses.; ethnicity.; sociology of religion.; SOCIAL SCIENCE -- Anthropology -- Cultural.; BIOGRAPHY & AUTOBIOGRAPHY -- Social Scientists & Psychologists.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; RELIGION -- General.; Religious minorities; East Indian Americans; East Indian Americans -- Ethnic identity; East Indian Americans -- Religion; East Indian Americans -- Social conditions; Ethnic relations; Ethnicity; Race relations; Religion; Religion and sociology; United States